2014
DOI: 10.1093/ntr/ntu066
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Assigned Interventions in a Randomized Trial of Internet and Telephone Treatment for Smoking Cessation

Abstract: A recent meta-analysis of Internet interventions for smoking cessation found mixed evidence regarding effectiveness. One explanation may be differential use of non-assigned cessation treatments-including other Internet programs-that either amplify or mask study intervention effects. We examined the impact of non-assigned treatment use on cessation outcomes in The iQUITT Study, a randomized trial of Internet and telephone treatment for smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Inconsistent with the results of Balmford, Borland, Benda, and Howard (2013) and Zbikowski et al (2011) – this website engagement did not differ in the two Web interventions (Web + Quitline= 90.4%; Web Only= 90.0%;). It is important to note further that the level of Web visits we observed was higher than in our previous Web-based smokeless tobacco cessation RCTs (Danaher et al, 2013; Danaher et al, 2015; Severson et al, 2008) as well as reported by Cobb and Graham (2014) for smokers who called a commercial Quitline (QuitNet.com) 25% of whom never logged into their assigned Web intervention.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Inconsistent with the results of Balmford, Borland, Benda, and Howard (2013) and Zbikowski et al (2011) – this website engagement did not differ in the two Web interventions (Web + Quitline= 90.4%; Web Only= 90.0%;). It is important to note further that the level of Web visits we observed was higher than in our previous Web-based smokeless tobacco cessation RCTs (Danaher et al, 2013; Danaher et al, 2015; Severson et al, 2008) as well as reported by Cobb and Graham (2014) for smokers who called a commercial Quitline (QuitNet.com) 25% of whom never logged into their assigned Web intervention.…”
Section: Discussioncontrasting
confidence: 51%
“…Similarly, they were asked about their use of smoking cessation medications Zyban® (Wellbutrin; Bupropion) and Chantix® (Verenicline). To determine the extent to which participants used non-assigned programs as recommended by Danaher et al (Danaher, Lichtenstein, McKay, & Seeley, 2009) and Cobb et al (Cobb & Graham, 2014), we also asked participants whether they received advice on how to quit from a health professional (physician, pharmacist, dentist/dental hygienist, and/or nurse), individual counseling (in person), group cessation program, other websites, hypnotherapy, or acupuncture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment utilization metrics were extracted at 3 months post-randomization, given that this is the period when website use is typically highest (4, 34). Self-report data were gathered via mixed-mode follow-up (online surveys, telephone for online non-responders).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked which methods they had used to quit in the past 3 months and were presented a list of common quit methods. 25 Participants were considered e-cigarette users if they selected "e-cigarettes" in response to this question or if they entered terms like "vapors," "vaping," "vape," or "ecigs" in the "other quit methods" open-ended response option.…”
Section: Methodsmentioning
confidence: 99%